2009
DOI: 10.1021/om900869p
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienyl Chromium β-Diketiminate Complexes: Initiators, Ligand Steric Effects, and Deactivation Processes in the Controlled Radical Polymerization of Vinyl Acetate

Abstract: dipp, 4) have been synthesized and used in polymerization experiments in addition to the previously known analogues with Ar = Ar = xyl, 1, or dipp, 5. The compounds were used as moderators for the polymerization of vinyl acetate (VAc) initiated by V-70, according to an OMRP mechanism. The alkylchromium(III) thermal initiator CpCr(nacnac xyl,xyl )(CH 2 CMe 3 ) (8) was synthesized from CpCr(nacnac xyl,xyl )(OTs) (7) and Mg(CH 2 CMe 3 ) 2 (dioxane), while 7 was obtained from CpCr(nacnac xyl,xyl )Cl (6) and AgOTs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 60 publications
5
87
0
Order By: Relevance
“…This reaction appears particularly accessible, at least on paper, following an HH addition, by β‐Y elimination with generation of a chain‐end unsaturation, see Scheme , which is mechanistically related to the β‐H elimination as a pathway to CCT. This pathway has been evidenced for VAc with control by a Cr system (transfer of the acetate group, vide infra),34 but transfer of Cl from a growing poly(vinyl chloride) chain can also be easily imagined.…”
Section: Controlled Polymerization Of Lamsmentioning
confidence: 89%
“…This reaction appears particularly accessible, at least on paper, following an HH addition, by β‐Y elimination with generation of a chain‐end unsaturation, see Scheme , which is mechanistically related to the β‐H elimination as a pathway to CCT. This pathway has been evidenced for VAc with control by a Cr system (transfer of the acetate group, vide infra),34 but transfer of Cl from a growing poly(vinyl chloride) chain can also be easily imagined.…”
Section: Controlled Polymerization Of Lamsmentioning
confidence: 89%
“…Steric conflict between N -aryl substituents and metal can also push the metal center out of the β-diketiminate ligand plane in some metal complexes, especially for early transition metals (Table 3.1.2). However, exceptions can be found in L R,Mes TiCl 2 , 52 L Me,R Cr(η 5 -Cp), 62, 63 L R,iPr FeNNFeL, 6, 41 [L Me,R Ni(μ-Cl)] 2 , 24, 25 L Me,R Cu(OAc), 64, 65 [LCu(μ-OH)] 2 , 44-46 [LCu(μ-S)] 2 , 66, 67 and L R,iPr Cu(CO). 68 …”
Section: Steric Effects On β-Diketiminatesmentioning
confidence: 99%
“…This is consistent with an equally facile reactivation of the dormant chains obtained after a heat-to-head and a head-to-tail monomer addition. In fact, it was shown that the VAc polymerization controlled by other mechanisms (ATRP, 47,48 RAFT, 49,50 ITP, 51 TERP, 52 and even OMRP with certain metal complexes as controlling agents 12 ) suffers from slowdown and/or -D increase with conversion, caused by the more difficult reactivation of the dormant chain obtained after the less frequent (1-2%) head-tohead addition. On the other hand, this problem does not affect the quality of control for the Co(acac) 2 -mediated polymerization.…”
Section: 32mentioning
confidence: 99%
“…The largest number of contributions makes use of cobalt complexes, after the first reports of the controlled polymerization of acrylates with porphyrin or glyoxime cobalt complexes by Harwood and Wayland 3,4 and a greater number of recent report for many monomers including VAc. 5 Certain complexes of Ti, [6][7][8][9] Mo, 10 Cr, [11][12][13] Os, 14,15 Mn, 16 and V, 17,18 have been successfully used as OMRP trapping agents, but it would be of interest to develop controlling systems based on iron in light of its low cost and biocompatibility.…”
mentioning
confidence: 99%